Knowledge and awareness on deceased donor skin harvest among intensive care units' staffs in national hospital of Sri Lanka - Sivasuganthan Kanesu; Gayan Ekanayake (Wolters Kluwer Medknow Publications, 2021)
Introduction: Skin coverage is a greatest challenge in severe burns when the donor sites are limited. Early skin cover is important to reduce morbidity and mortality in severe burns. We use to harvest skin from cadavers at intensive care units (ICUs) for temporary cover of excised burn wounds. As we do not get enough cadaveric donations from ICUs, we plan to conduct this study to identify awareness and knowledge on it. Methods: We collected data from doctors and nurses working in surgical ICUs (general surgical, accident and emergency, and neurosurgical) by a self-administered questionnaire. Then, we analyzed the results by SPSS 19 data package. Results: One hundred and forty participants responded to our questionnaire including 118 nurses and 22 doctors. Only 40% (n = 48) of nurses and 60% (n = 13) of doctors were aware about cadaveric skin donation. Only 31% (n = 44) knew that tissue or blood matching is not needed for it. 88% (n = 124) knew that graft is mainly taken from thighs. Some responded as skin of the patients with comorbidities cannot be used for the transplant. Twelve percent (n = 18) knew whom to contact when the patient for cadaveric skin transplant is identified. Only 17% (n = 24) thinks that it does not cause much disfigurement to the cadaver. Thirteen percent (n = 18) did not know any details about skin donation. Conclusion: There is a knowledge deficit in ICU staffs regarding awareness and knowledge on cadaveric skin harvest. We could not compare the doctors and nurses as there were less participants in doctors. In ICUs, an awareness campaign is required. In future, this concept should be assessed in general public as well.